Solve Graphically -15(x+3)+5(4x-3)=4(x-4)+12

Math
-15(x+3)+5(4x-3)=4(x-4)+12
Simplify -15(x+3)+5(4x-3).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-15x-15⋅3+5(4x-3)=4(x-4)+12
Multiply -15 by 3.
-15x-45+5(4x-3)=4(x-4)+12
Apply the distributive property.
-15x-45+5(4x)+5⋅-3=4(x-4)+12
Multiply 4 by 5.
-15x-45+20x+5⋅-3=4(x-4)+12
Multiply 5 by -3.
-15x-45+20x-15=4(x-4)+12
-15x-45+20x-15=4(x-4)+12
Simplify by adding terms.
Tap for more steps…
Add -15x and 20x.
5x-45-15=4(x-4)+12
Subtract 15 from -45.
5x-60=4(x-4)+12
5x-60=4(x-4)+12
5x-60=4(x-4)+12
Simplify 4(x-4)+12.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
5x-60=4x+4⋅-4+12
Multiply 4 by -4.
5x-60=4x-16+12
5x-60=4x-16+12
Add -16 and 12.
5x-60=4x-4
5x-60=4x-4
Graph each side of the equation. The solution is the x-value of the point of intersection.
No solution
Solve Graphically -15(x+3)+5(4x-3)=4(x-4)+12

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top